Thermal Environment inside a Tunnel after Thermobaric Explosion - Fei Chen; Jinfeng Mao; Jin Zhou; Pumin Hou; Liyao Liu; Shangyuan Chen (Shock and Vibration)
The outstanding thermal damage effect of thermobaric explosive (TBX) is enhanced in closed or semiclosed spaces, which may pose a serious threat to the security of people sheltered in tunnels or other protective engineering. In order to investigate the thermal environment inside a tunnel after thermobaric explosion, we developed a damage evaluation method for the thermal radiation of explosion fireballs in tunnels; secondly, the air temperature distribution inside a tunnel shortly after explosion was theoretically analyzed; finally, the dynamic thermal environment after the explosion and the influences of TBXs mass and initial ground temperature on it in cases of open and blocked tunnels were numerically simulated with the FLUENT software. The results show that the fireball thermal radiation damage occurs mainly in the vicinity of the explosion source. The air temperature inside a tunnel shortly after the explosion decreases continuously with increasing distance from the explosion source and finally reaches the initial air temperature. The decay rate of air temperature inside a tunnel is slower in the blocked case, which increases the probability of causing a secondary fire disaster. The increase of explosive mass and the initial ground temperature favor the high-temperature performance of TBX, especially for the blocked tunnel.